Analisis Penerapan Basis Kas dan Akrual Terhadap Laporan Keuangan Pada Pemerintah Kota Malang - Baity, Nurul; Bahri, Syamsul; Puspitosarie, Endah (CV. ITTC INDONESIA, 2025)
This study aims to analyze the application of cash basis and accrual basis in the presentation of Malang City Government financial statements, identify sections of the report that still use cash basis and those that are accrual-based, and evaluate the suitability of financial statement preparation with accrual-based Government Accounting Standards (SAP). This study uses a descriptive qualitative method with a content analysis approach to the Malang City Government's 2023 Budget Realization Report (LRA). The results of the study show that the Malang City Government has implemented SAP in accordance with the provisions of PP No. 71 of 2010 and Permendagri No. 64 of 2013. The Budget Realization Report still uses a cash basis, while other reports such as the Balance Sheet, Operational Report, and Notes to the Financial Statements use an accrual basis. The preparation of financial statements has generally met the principles of accountability, transparency, and comparability, although the full implementation of accrual accounting still needs to be improved, especially in the recognition and disclosure of non-cash transactions. Thus, the Malang City Government has consistently implemented a cash-toward-accrual system as part of the implementation of accrual-based SAP in regional financial management.